Synthesis of Amino-Impregnated ZIF-8 for CO2 Adsorption - Yahya, N.H.B. (Institute of Physics Publishing, 2017)
Zeolitic imidazolate framework-8 (ZIF-8) is well known for its high thermal stability, high surface area and remarkable water stability as compared to the other adsorbents. However, ZIF-8 shows relatively low CO2 capture ability. In this work, ZIF-8 is modified with amino-groups via wetness impregnation method and the performance of the resultant adsorbents in CO2 capture is investigated. Two different types of amino-groups including tetraethylenepentamino (TEPA) and pentaethylenehexamino (PEHA) were used. The concentrations of TEPA and PEHA were prepared at 30, 50 and 70 volume in chloroform solution, respectively, prior to impregnation over ZIF-8. The Fourier transform infrared (FTIR) results showed that, successful incorporation of amino groups into ZIF-8 was achieved. Meanwhile, based on SEM images, severe agglomeration of particles was observed for 50 and 70 TEPA and PEHA-impregnated ZIF-8. Subsequently, it was found that ZIF-8 impregnated with 30 TEPA showed the highest CO2 adsorption capacity of 1.9983 mmol g-1 as compared the other adsorbents prepared in this work. This has signified the improvement of CO2 adsorption capacity by using amino-impregnated ZIF-8, which was up to 199.6 compared to the parent ZIF-8. Overall, the adsorbents developed in the present work are potential to be used in the industrial CO2 adsorption processes. © Published under licence by IOP Publishing Ltd.